Symbols in traditional dance: A study of Nkwanwite dance - Akas, Nicholas C. (Journal of Gender and Power, 2020)
The use of iconic symbols during traditional performances (dance) has remained an indispensable tool. The major problem facing the use of signifying symbols during performances is because they are seen as mere performative enhancer. These assumptions might be generally accepted, but in core dance scholarship it can be argued for or against, but this paper stands against its wrong perceived nature as mere performative enhancer. The aim of this paper is to interpret some of the signifying symbols used in dance in order to understanding their socio-cultural essence. This paper would analyze the signifying symbols used in Nkwanwite traditional dance for the following reasons: (a) To acknowledge the use of cultural symbols as part of people’s mythology belief. (b) To interpret, analyze and document the signifying symbols as a socio-communicative tool. (c) To give each of the signifying symbols relevance and interpretation in dance. In order to achieve this Sense Making Theory would be used as theoretical frame work to interrogate the essence of the signifying symbols. Findings show that, due to lack of interpretation and documentation on the use of signifying symbols in dance. It is gradually going into extinction as mere props. The paper concludes that non dance scholars should cherish and appreciate the use of symbols in dance as communicative tool.